Perception of Tele-dermatology Consultation among Social Media Users - Sishir Poudel; Sushan Pokharel; Sudha Agrawal; Suchana Marahatta (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction: Tele-dermatology is significant for faster delivery of health care particularly in geographically isolated areas.